CrossTalk opposing view: Bradycardia in the trained athlete is attributable to a downregulation of a pacemaker channel in the sinus node - D'Souza, A.; Sharma, S.; Boyett, M. R. (The Journal of Physiology, 2015)
It is well known that athletes have a low resting heart rate (bradycardia). The bradycardia can be moderate to severe: reports of heart rates of 40-60 beats min-1 in athletes are common (Boyett et al. 2013), and Jensen-Urstad et al. (1997) reported heart rates of <30 beats min-1 in elite athletes at night. Consistent with this, S. Sharma has studied 142 elite cyclists and rowers and observed heart rates over the range 30-70 beats min-1; the distribution of heart rates in the athletes (and for comparison in a normal population) is shown in Fig. 1. The resting heart rate is easy to measure and it is clear that athletes use the resting heart rate as a measure of fitness and speak of it in terms of pride and bravado. This is despite evidence that veteran athletes are more likely to need an electronic heart pacemaker fitted in later life (Baldesberger et al. 2008). The bradycardia is widely believed to be the result of high vagal tone; this is a natural assumption because high vagal tone will reduce the heart rate. However, despite this widespread belief, efferent vagal nerve activity to the heart's pacemaker (the sinus node) has never been recorded. It is not obvious how it could be measured, because the vagus nerve carries afferent as well as efferent nerve fibres. Because of this, the scientific community uses what is assumed to be a surrogate of vagal nerve activity to the sinus node, heart rate variability. Heart rate variability is a beat-to-beat variability in the heart rate and is assumed to be the result of stochastic fluctuations in autonomic nerve activity to the sinus node and changes in heart rate variability are assumed to represent changes in this. PubMed lists more than 17,000 publications concerned with heart rate variability. Heart rate variability is higher in athletes (Aubert et al. 2003) and this is taken as evidence of high vagal tone in athletes, and this is then assumed to be responsible for the bradycardia. However, a causative link between autonomic nerve activity and heart rate variability has never been demonstrated (for reasons discussed above).